Power versus strength-power jump squat training: Influence on the load-power relationship - Cormie, P.; McCaulley, G. O.; McBridge, J. M. (Medicine & Science in Sports & Exercise, 2007)
Purpose: The purpose of this investigation was to compare the impact of power training and strength-power training on the load-power relationship in the jump squat.